Extent of Implementation of National Entrepreneurship Curriculum in Tertiary Institutions as Perceived by Educators - Noeleen, Obi, Mary; C., Okekeokosisi, Johnbosco.O. (American Journal of Education and Learning, 2018)
The study investigated on the extent of implementation of National Entrepreneurship curriculum in tertiary institutions as perceived by educators. Federal university lectures in south-south geopolitical zone of Nigeria constituted the population. A total of 531 federal university lectures (202 males and 329 females) made up the sample size. Proportionately stratified random sampling technique was used to sample three out of five Nigerian federal universities in south-south geopolitical zone. In each of the three Nigerian federal universities, 10% of the entire population of lectures in each Nigerian federal university was used for the study. Thus a sample of 531 university lectures was drawn and used for the study. Four research questions and one null hypotheses guided the study. A 19 item questionnaire titled “Entrepreneurship Curriculum Implementation in Tertiary Institutions As Perceived by Educators (ECITIAS PBE)’’ was developed by researchers. The developed questionnaire guided the study. Mean, Standard deviation and t-test were used for data analysis. The result indicated that the extent of adherence to entrepreneurship curriculum is of low extent. Based on these findings, the researcher recommended that more efforts should be made by the federal government, state government, local government and communities to provide adequate and necessary facilities for schools so that the educators will have access to practice with them even after they have gone for training so as not to lose the knowledge they gained from training. Awareness creation on the relevance of entrepreneurship curriculum for its effective implementation for its restructuring and provision of facilities through newspaper adverts, radio and television jungles, on line publications etc.